2012
DOI: 10.1002/adfm.201102669
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Lithium Storage with High Mobility at Structural Defects in Amorphous Molybdenum Dioxide Electrode

Abstract: This work demonstrates that structural defects in amorphous metal oxide electrodes can serve as a reversible Li+ storage site for lithium secondary batteries. For instance, molybdenum dioxide electrode in amorphous form (a‐MoO2) exhibits an unexpectedly high Li+ storage capacity (up to four Li per MoO2 unit), which is larger by a factor of four than that for the crystalline counterpart. The conversion‐type lithiation is discarded for this electrode from the absence of Mo metal and lithium oxide (Li2O) in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(128 citation statements)
references
References 29 publications
7
120
1
Order By: Relevance
“…7 A coin-type cell with amorphous MoO 2 electrode showed particularly higher capacity and better rate capability than that of the cell with crystalline MoO 2 . 8 Ku et al reported that the cell performance was improved because the structural defects in amorphous MoO 2 acted as a Li + storage site. Moreover, amorphous phosphorus-carbon composite electrodes in the liquid-type cells using an organic liquid electrolyte showed a high reversible capacity about 1740 mAh g ¹1 for 100 cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A coin-type cell with amorphous MoO 2 electrode showed particularly higher capacity and better rate capability than that of the cell with crystalline MoO 2 . 8 Ku et al reported that the cell performance was improved because the structural defects in amorphous MoO 2 acted as a Li + storage site. Moreover, amorphous phosphorus-carbon composite electrodes in the liquid-type cells using an organic liquid electrolyte showed a high reversible capacity about 1740 mAh g ¹1 for 100 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…However, reported literature on amorphous electrodes is limited, compared to those of crystalline electrodes. Within that literature amorphous oxide based electrodes, [7][8][9][10][11] amorphous sulfide based electrodes [12][13][14][15][16][17] and amorphous phosphorus based electrodes 18,19 were reported. For example, amorphous V 2 O 5 exhibited better rechargeability than crystalline V 2 O 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Surface defect such as surface vacancies or voids is a common phenomenon for nanomaterials. It has been reported that the defects in Li 4 Ti 5 O 12 [44] and amorphous MoO 2 [45] can serve as Li þ storage sites for improved lithium storage capacity and rate performance. Hence, the increased initial capacity of Li 4 Ti 5 O 12 and Li 4 Ti 5 O 12 -rutile TiO 2 nanosheets might also originate from the lattice distortion resulted from the surface vacancies or voids.…”
Section: Resultsmentioning
confidence: 99%
“…(2) The structural defects in amorphous metal oxide can act as reversible Li + storage sites [46]. (3) The nanometer-level crystal size of metal oxide provides many surface sites for Li + storage due to the expansion of surface area [47].…”
Section: Electrochemical Measurementmentioning
confidence: 99%